Hydrothermal Sintering for Densification of Silica. Evidence for the Role of Water. Issue 4 (April 2018) - Ndayishimiye, Arnaud; Largeteau, Alain; Mornet, Stéphane; Duttine, Mathieu; Dourges, Marie-Anne; Denux, Dominique; Verdier, Marc; Gouné, Mohamed; Hérisson de Beauvoir, Thomas; Elissalde, Catherine; Goglio, Graziella
Abstract: We present hydrothermal sintering as a smart route to densify ceramics at low temperature. Home-made silica nanoparticles naturally hydrated, partially and quasi -fully dehydrated were submitted to hydrothermal sintering (190 MPa, 300 °C, 90 min) without additional water. Their morphology and surface chemistry strongly influence their packing and then the mechanical-chemical effects responsible for densification involving dissolution-precipitation mechanisms. The connection between the porosity and the starting compact packing was pointed out. Moreover, the influence of additional chemical effects was highlighted as the polycondensation of protruding silanols favors the formation of interparticle necks via the creation of polysiloxane bonds. When external water is added, the filling of the mesopores is nearly fully achieved but large residual macropores initiated in the early stage of sintering are remaining. The compactness of the as-obtained ceramic is 73.6%. We also demonstrate the influence of water on the mechanical and deformation behavior of the samples.